Republic of Lebanon : Accounting and Auditing - World Bank (Washington, DC, 2013)
Despite Lebanon's overall commendable progress in implementing international standards, there are still compliance gaps of varying degrees in both accounting and auditing practices. There is less gap in listed companies and banks; a greater gap appears in other companies with determinants based on size and who is performing the audit. These gaps stem primarily from shortcomings in professional education and training in Lebanon. When the Lebanese Association for Certified Public Accountants was established in 1994, all applicants, who sought license to practice, were certified without examination. More importantly, no enforcement mechanism exists to ensure International Accounting Standards (IAS) compliance, except in the banking sector. Although many audit firms make effort to perform audits in accordance with International Standards on Auditing (ISA), quality of audits varies significantly. The Order on Auditing, issued by the Minister of Finance, does not cover regulation or supervision of the auditing profession and does not mention enforcement regulations or the monitoring of ISA compliance. This report provides recommendations for an action plan, with particular focus on developing practical implementation guidelines; strengthening enforcement mechanisms; upgrading accounting curricula and increasing training arrangements and opportunities for practicing auditors; and establishing a system to perform quality control reviews of audit practices.